Microtomography evaluation of dental tissue wear surface induced by in vitro simulated chewing cycles on human and composite teeth - Rossella Bedini; Raffaella Pecci; Gianluca Notarangelo; Francesca Zuppante; Salvatore Persico; Fabio Di Carlo (Istituto Superiore di Sanità, 2012)
In this study a 3D microtomography display of tooth surfaces after in vitro dental wear tests has been obtained. Natural teeth have been compared with prosthetic teeth, manufactured by three different polyceramic composite materials. The prosthetic dental element samples, similar to molars, have been placed in opposition to human teeth extracted by paradontology diseases. After microtomography analysis, samples have been subjected to in vitro fatigue test cycles by servo-hydraulic mechanical testing machine. After the fatigue test, each sample has been subjected again to microtomography analysis to obtain volumetric value changes and dental wear surface images. Wear surface images were obtained by 3D reconstruction software and volumetric value changes were measured by CT analyser software. The aim of this work has been to show the potential of microtomography technique to display very clear and reliable wear surface images. Microtomography analysis methods to evaluate volumetric value changes have been used to quantify dental tissue and composite material wear.